ISSP 2000 - Environment II: Sweden - Edlund, Jonas; Svallfors, Stefan (Umeå University, 2009)
This survey is the Swedish part of the 2000 'International Social Survey Program'. ISSP is an ongoing program of cross-national collaboration. Formed in 1983, the group develops topical modules dealing with important areas of social science as supplements to regular national surveys. The topic of year 2000 was 'Environment', and this was the second survey exploring this topic. The initial survey on this topic was in 1993, a year before the first Swedish ISSP survey. The topic was explored a third time in 2010 (SND 0887), hence the second time in Sweden.

In this survey the respondents were asked to comment on various topics regarding nature and the environment, including the role of science and scientific solutions to environmental problems and protection of the environment through higher prices of goods, higher taxes or cuts in the standard of living. In addition, respondents were asked to estimate the effects of air pollution, pesticicides and chemicals used in farming, and modifications of genes of certain crops on themselves, their families, and the environment. Additional information was elicited regarding measures respondents were taking to protect the environment. The respondents also had to indicate their trust in information about casuses of pollution given by different groups. A number of questions dealt with opinions on the Swedish taxes; the pressure of taxation in general, and for various income brackets; willingness to pay more tax if the money was spent on different specific areas; charges when using public services instead of paying through taxes. Respondents also had to state if they felt a need for private insurances to supplement the public welfare system. Demographic variables include respondent´s occupation, trade union affiliation, education, housing, income, marital status, spouse´s occupation, income, number of children, citizenship of parents, and political preferences.

Purpose:

ISSP aims to design and implement internationally comparable attitude surveys. The study in 2000 investigating Environment.

Detta är den svenska studien inom det internationella forskningsprojektet ISSP. Temat för studien 2000 är ”Environment”. Detta är andra gången studien genomförs på det här temat och har sedan genomförts ytterligare en gång på samma tema (SND 0887).

International Social Survey Program, ISSP, är ett globalt forskningsprojekt som har till uppgift att konstruera och genomföra internationellt jämförbara attitydstudier. Sedan 1985 har attityddata årligen samlats in och utgör nu en databas som är fritt tillgänglig för forskarsamhället. I dagsläget är 48 länder, från sex olika världsdelar, involverade i projektet. Genom bredden av medlemsländer skapas möjlighet till jämförelser i flera dimensioner. Det finns möjligheter att både jämföra länder som har en likartad samhällsstruktur och historia, och länder som skiljer sig påtagligt från varandra.

Sverige har varit medlem i ISSP sedan 1992 och det är Sociologiska intuitionen vid Umeå universitet som är huvudman för studierna i Sverige.

Sedan starten 1985 har attityder från flera olika områden undersökts. Vissa områden har återkommit genom åren, vilket gör det möjligt att även jämföra dem över tid.

Syfte:

ISSP har som syfte att konstruera och genomföra internationellt jämförbara attitydstudier. Studien för 2000 undersöker åsikter miljön.
ISSP 2000 - Åsikter om miljön
Keywords: environment; miljö; social welfare; social välfärd; environmental changes; miljöförändringar; environmental degradation; miljöförstörelse; science; vetenskap; pollution; föroreningar; genetic engineering; genteknik; trust; förtroende; environmental conservation; miljöbevarande; taxation; beskattning; CORS; CORS; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Social welfare systems/structures; Sociala välfärdssystem/-strukturer; Social Sciences; Samhällsvetenskap; Sociology; Sociologi